BASEL III – A new approach to improve international financial stability - BAICU, Claudia Gabriela (Annals of Spiru Haret University. Economic Series, 2010)
In its first part, the article highlights the factors standing at the basis of the modification of the general framework of development of the banking activity in the last decades and the main trends that manifested on the international banking market until the global financial crisis. Thenceforth, the main lessons learned from the global financial crisis for the regulation and supervision authorities are presented. The final part of the article concerns the Basel Committee answer to the global financial crisis, concretised in a reform programme regarding the regulatory framework of the banking activity. The improvements and news brought by the Basel III reform programme take into account the flaws revealed by the global financial crisis and have the purpose to strengthen the stability of the international financial system.